2012
DOI: 10.1515/htmp-2012-0002
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal Reductive Upgrading of a Bauxite Ore Using Microwave Radiation

Abstract: The utilization of microwave radiation as the energy source for the carbothermal reductive upgrading of a bauxite ore was investigated. The bauxite ore was mechanically mixed with carbon and reacted in a quartz crucible in a multimode cavity. The iron oxide in the bauxite ore was reduced to magnetite and/or iron and the magnetic fraction was separated using a Davis Tube Tester. Three experimental arrangements were utilized: (i) microwaving of the mixture, (ii) microwaving of the mixture plus charcoal layers un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…As Lu et al [38] explained in their work, the hercynite is an unavoidable product. During the roasting process, the hematite can be reduced to magnetite [19] by the carbon source, but in the presence of alumina, it can be transformed also into hercynite.…”
Section: Carbon Source Addition To Brmentioning
confidence: 97%
See 1 more Smart Citation
“…As Lu et al [38] explained in their work, the hercynite is an unavoidable product. During the roasting process, the hematite can be reduced to magnetite [19] by the carbon source, but in the presence of alumina, it can be transformed also into hercynite.…”
Section: Carbon Source Addition To Brmentioning
confidence: 97%
“…The influence of microwave energy on the sample, the effect of irradiation time, and the addition of carbon source to BR (C/BR ratio) were the parameters investigated to find the optimized combination to convert iron oxides into metallic iron, according to the sequence of Fe 2 O 3 →Fe 3 O 4 →FeO→Fe [31,37,38].…”
Section: Microwave Roasting Process Optimizationmentioning
confidence: 99%
“…In practice, it means that the sample must be under hydrogen flow so that the amount of H 2 O that is released becomes low enough that the gas mixture in the bed reaches the conditions for the hercynite reduction. As T. Lu et al have observed, temperatures greater than 1000 °C are required for the reduction of hercynite using carbon and carbon monoxide as reductants [26]. Observing no hercynite reduction from our sample for temperatures higher than 960 °C may be due to not enough time at this temperature after its formation, if we assume that the H 2 /H 2 O ratio is large enough for its reduction at the latest minutes of the reduction step.…”
Section: Kinetics Of Iron Oxide Reductionmentioning
confidence: 56%
“…Microwave heating provides several advantages through savings in energy, space and time, and a reduction in the environmental impact of material processing. There are have lots of literatures referred to the microwave reduction of oxides ores, such as magnetite, 13) hematite, 14) vanadium titano-magnetite, 15) steel making slag and sludge, 16) nickeliferous silicate laterite, 17) malachite concentrate, 18) bauxite ore, 19) and so on. In the present work, the reduction of coke-bearing oolitic hematite pellets were conducted at temperature of 1 273-1 523 K in a temperature controllable microwave cavity with the output power of 0-1.5 kW.…”
Section: Microwave Carbothermic Reduction Of Oolitic Hematitementioning
confidence: 99%